Daya Dukung dan Laju Pertumbuhan Microcystis Hasil Isolasi dari Waduk Sutami pada Berbagai Variasi Konsentrasi Nitrat dan Fosfat dalam Medium Selektif B-12 - Catur Retnaningdyah; Suharjono Suharjono; Agoes Soegianto; Bambang Irawan (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
The main objective of this research was to calculate the carrying capacity and growth rate ofisolated Microcystis result in Sutami reservoir on a variety of nitrate and phosphateconcentrations in the B-12 selective medium. Research was conducted in the laboratory withpure experiments using completely randomized factorial design with factors of nitrateconcentration variation (8, 16, 32, and 64 ppm) and phosphate (0.2, 0.4, 0.8 and 1.6 ppm) in B-12medium. Repetition of the study was conducted three times at the same time. Microcystispopulation abundance which was counted every day until the stationary phase (day +30) wasused to calculate the rate of growth (β) and maximum abundance of Microcystis can besupported by each medium treatment (γ). The results showed that the growth rate of Microcystiswas not significantly influenced by levels of phosphate in the medium but significantly positivelycorrelated with increasing nitrate concentration in the medium. Carrying capacity or themaximum abundance (γ) of Microcystis was influenced by the combination of nitrate andphosphate in the B12 medium. Concentration of phosphate 0.4 ppm in medium combined withnitrate 8−64 ppm could support the highest abundance of Microcystis.